2015
DOI: 10.1002/marc.201500587
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Intramolecular and Intermolecular Catalyst‐Transfer Suzuki–Miyaura Condensation Polymerization: Synthesis of Boronate‐Terminated π‐Conjugated Polymers Using Excess Dibromo Monomers

Abstract: The Suzuki-Miyaura coupling polymerization of dibromoarene 1 and arylenediboronic acid (ester) 2 with a Pd catalyst having a high propensity for intramolecular catalyst transfer is reported. The polymerization of excess 1 with 2 affords high-molecular-weight π-conjugated polymer having boronic acid (ester) moieties at both ends, contrary to Flory's principle. This unstoichiometric polycondensation behavior is accounted for by intramolecular transfer of the Pd catalyst on 1. In the polymerization of 1 and 2 hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Since we found that t Bu 3 PPd undergoes intramolecular transfer on several functional groups, we applied this chemistry to Suzuki–Miyaura unstoichiometric polycondensation of 1.3 equivalent of 1 and 1.0 equivalent of phenylenedibronic acid 5 in the presence of t Bu 3 PPd G2 precatalyst (Scheme , Table ). Intramolecular catalyst transfer on 1 is expected to afford high‐molecular‐weight polymer with boronic acid moieties at both ends even if excess 1 is used, as in the case of unstoichiometric Suzuki–Miyaura polycondensation of aromatic monomers . Indeed, polycondensation using 1 a – d , and 1 g , which exhibited intramolecular catalyst transfer in the reaction with 2 (Table ), afforded high‐molecular‐weight polymer ( M n ≥7500) (Table , entries 1–4, and 7), and the polymer obtained in the initial stage appeared to have boronic acid moieties at both ends (Figures S12, S14, S17, and S20, Supporting Information), although the polymer formed from 1 g and 5 did not show any peaks in the MALDI‐TOF mass spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Since we found that t Bu 3 PPd undergoes intramolecular transfer on several functional groups, we applied this chemistry to Suzuki–Miyaura unstoichiometric polycondensation of 1.3 equivalent of 1 and 1.0 equivalent of phenylenedibronic acid 5 in the presence of t Bu 3 PPd G2 precatalyst (Scheme , Table ). Intramolecular catalyst transfer on 1 is expected to afford high‐molecular‐weight polymer with boronic acid moieties at both ends even if excess 1 is used, as in the case of unstoichiometric Suzuki–Miyaura polycondensation of aromatic monomers . Indeed, polycondensation using 1 a – d , and 1 g , which exhibited intramolecular catalyst transfer in the reaction with 2 (Table ), afforded high‐molecular‐weight polymer ( M n ≥7500) (Table , entries 1–4, and 7), and the polymer obtained in the initial stage appeared to have boronic acid moieties at both ends (Figures S12, S14, S17, and S20, Supporting Information), although the polymer formed from 1 g and 5 did not show any peaks in the MALDI‐TOF mass spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Dry tetrahydrofuran (THF, stabilizer-free, Kanto, Tokyo, Japan) and distilled water (Wako, Tokyo, Japan) were used as received. Dibromoazobenzene 1b [18] and phenylenediboronic acid 6a [11] were prepared according to the literature.…”
Section: Methodsmentioning
confidence: 99%
“…When this t-Bu 3 PPd(0) catalyst, which has a propensity for intramolecular catalyst transfer on a π-electron face, was used for Suzuki-Miyaura coupling polymerization of dibromoarene and arenyldiboronic acid ester (AA + BB polycondensation), high-molecular-weight π-conjugated polymer with a boronate moiety at both ends was obtained, even though excess dibromoarene was used [11]. This unstochiometric polycondensation behavior is accounted for by successive substitution of the bromides in dibromoarene with arenyldiboronic acid ester or oligomers having boronate moieties at Catalysts 2017, 7,195; doi:10.3390/catal7070195 www.mdpi.com/journal/catalysts both ends through intramolecular transfer of the Pd catalyst on the π face of dibromoarene.…”
Section: Introductionmentioning
confidence: 99%
“…Kramer and co‐workers synthesized regio‐regular/irregular cyclopentadithiophene–pyridylthiadiazole alternating copolymers, and found that the hole transport property ( μ e ) of the regio‐regular alternating copolymer was approximately 100 times better than that of the regio‐irregular copolymer . Moreover, we have recently found that Suzuki–Miyaura coupling polymerizations of diboronic acid ester and dibromoarene in the presence of t Bu 3 PPd precatalyst affords high‐molecular‐weight boronate‐terminated π‐conjugated polymers, even if excess dibromoarene is used, and we synthesized a fluorene–benzothiadiazole ( D –A) alternating copolymer with terminal boronate groups by using this method . Higashihara and co‐workers reported similar Stille coupling copolymerizations of distanylthiophene (D) and excess dibromonaphthalenediimide (A), but did not mention the polymer end groups …”
Section: Introductionmentioning
confidence: 99%
“…[7] Moreover,w eh ave recently found that Suzuki-Miyaura coupling polymerizations of diboronic acid ester and dibromoarene in the presence of tBu 3 PPd precatalyst [8] affords high-molecular-weight boronate-terminated p-conjugated polymers, even if excess dibromoarene is used, and we synthesized af luorene-benzothiadiazole (D-A) alternating copolymer with terminal boronate groups by using this method. [9] Higashihara and co-workers reporteds imilar Stille coupling copolymerizationso fd istanylthiophene (D) and excess dibromonaphthalenediimide (A), but did not mention the polymer end groups. [10] Regarding the control of molecular weight and dispersity of D-A p-conjugated alternating copolymers, catalyst-transfer condensation polymerization (CTCP), which proceeds in ac hain-growthp olymerization manner,o fm onoaromatic AB monomers through Kumada-Tamao, [11] Suzuki-Miyaura, [12] Negishi, [13] Murahashi, [14] or Stille [15] couplingr eactions has been extendedt oC TCP of D-A biaryl and D-A-D teraryl monomers to afford D-A p-conjugated alternating copolymers with defined molecular weightand low dispersity.Kiriy and co-workers first demonstrated that thiophene-thiophene( D-D) biaryl monomers underwent Ni-catalyzed Kumada-Tamao CTCP.…”
mentioning
confidence: 99%